Programming Languages and Systems 6th Asian Symposium, APLAS 2008, Bangalore, India, December 9-11, 2008, Proceedings - Ramalingam, G. (Programming and Software Engineering, 2008)
This book constitutes the refereed proceedings of the 6th Asian Symposium on Programming Languages and Systems, APLAS 2008, held in Bangalore, India, in December 2008. The 20 revised full papers presented together with 3 invited talks were carefully reviewed and selected from 41 submissions. The symposium is devoted to all topics ranging from foundational to practical issues in programming languages and systems. The papers cover topics such as semantics, logics, foundational theory, type systems, language design, program analysis, optimization, transformation, software security, safety, verification, compiler systems, interpreters, abstract machines, domain-specific languages and systems, as well as programming tools and environments.